PENGARUH KOMITMEN MANAJEMEN PUNCAK DALAM KUALITAS PELAYANAN BPRS TERHADAP KEPUASAN NASABAH [Studi Pada BPRS Botani (Bina Rahmah) Dramaga Bogor] - Pitria Ningsih; Tubagus Rifqy Thantawi; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
ABSTRACT One of the bank's problems is regarding service. The investigative questions include: 1) Does the customer service, counter and marketing of BPR Syariah together contribute to customer satisfaction? 2) Does the top management's commitment to BPR Syariah Botani service quality provide satisfaction for satisfaction? The aims of this research are: 1) To find out the effect of customer service, counter and BPRS marketing on sales satisfaction. 2) Prioritizing top management commitment to service quality of BPR Syariah Botani for credit satisfaction. This study uses quantitative analysis and the analysis used is multiple linear regression. The sampling technique used is simple random sampling. The research sample used was BPRS Botani and 100 respondents from the general public. The results of this study indicate that the adjusted R-squared value is 0.607 (60.7%). Priority satisfaction for CS, counter and marketing is 60.7%. The remaining 39.3% is approved by factors other than model. Thus the research hypothesis